2022
DOI: 10.3390/ijerph192315663
|View full text |Cite
|
Sign up to set email alerts
|

International Survey of Specialist Fetal Alcohol Spectrum Disorder Diagnostic Clinics: Comparison of Diagnostic Approach and Considerations Regarding the Potential for Unification

Abstract: Fetal alcohol spectrum disorder (FASD) is a prevalent neurodevelopmental condition. Despite FASD being recognized as a clinical disorder there is no globally agreed set of diagnostic criteria. Accurate and timely diagnosis of FASD is imperative to inform clinical care, optimize outcomes for individuals accessing assessments and their families, as well as for research and prevention strategies. To inform movement towards a unified approach, the present study aimed to capture an international perspective on curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Of the included studies, eight were conducted in Canada, one in Australia, and two were international surveys. Six of the studies were based on information collected through questionnaires and surveys of FASD clinics (Clarren et al, 2011; Clarren & Lutke, 2008; Dugas et al, 2022; Panton et al, 2022; Peadon et al, 2008; Reid, Shanley, et al, 2022), three studies were summaries or critical reviews of specific FASD clinics (McFarlane, 2011; McFarlane & Rajani, 2007; Temple et al, 2015), one was a retrospective chart review of clinical data (Patel et al, 2019), and one study reported a nonexperimental cost estimation model (Popova et al, 2013). An overview of the included studies can be found in Table S3 and a visual summary of the included studies, and the subtopics addressed by the included studies can be found in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, eight were conducted in Canada, one in Australia, and two were international surveys. Six of the studies were based on information collected through questionnaires and surveys of FASD clinics (Clarren et al, 2011; Clarren & Lutke, 2008; Dugas et al, 2022; Panton et al, 2022; Peadon et al, 2008; Reid, Shanley, et al, 2022), three studies were summaries or critical reviews of specific FASD clinics (McFarlane, 2011; McFarlane & Rajani, 2007; Temple et al, 2015), one was a retrospective chart review of clinical data (Patel et al, 2019), and one study reported a nonexperimental cost estimation model (Popova et al, 2013). An overview of the included studies can be found in Table S3 and a visual summary of the included studies, and the subtopics addressed by the included studies can be found in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…For example, those in the Attention needs group generally presented with lower average significant neurodevelopmental impairment, and with lower rates of mental and physical health needs, with the exception of ADD/ADHD, and difficulties related to sleep and sensory issues. Importantly, this group included a subset of younger school‐aged children, including those designated At Risk, possibly aligning with previously reported challenges confirming an FASD diagnosis during the earlier preschool years (Hanlon‐Dearman et al, 2020; McLachlan et al, 2015), and ongoing discussion in the field about the best fitting approach to FASD diagnostic criteria and diagnosis (e.g., Coles, Bandoli, et al, 2022; Hemingway et al, 2019; Reid et al, 2022). Younger children who present with confirmed PAE and/or all three sentinel facial features should be referred for a complete neurodevelopmental assessment at an age‐appropriate or future time, and those designated At Risk should receive the same services as those with an FASD diagnosis, with alignment to their current needs (Cook et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have explicitly assessed whether these needs differ based on neurodevelopmental profile or diagnostic features, with a small number finding differences (e.g., Chasnoff et al, 2010; Coles, Grant, et al, 2022; Lange et al, 2019; Mattson & Riley, 2000). Further, poor diagnostic agreement across the FASD spectrum when applying differing diagnostic guidelines and approaches complicates comparisons across systems and jurisdictions, particularly in the absence of a single ‘gold standard’ diagnostic approach (Coles et al, 2016; Coles, Bandoli, et al, 2022; Hemingway et al, 2019; Reid et al, 2022). Taken together, these findings underscore a continued need to better characterize ‘within‐group’ differences in neurodevelopmental and clinical needs for children and adolescents with PAE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a current obstacle to broad collaboration in the FASD field regarding the topic of diagnosis that needs to be acknowledged is the disparities in the established research groups. This was highlighted in a recent study I was involved with that undertook an international survey of FASD specialist diagnostic clinics to explore barriers and facilitators to developing a unified approach to FASD diagnosis (Reid et al, 2022). The vast majority of respondents (90.9%; n = 50) believed that a unified approach to diagnosis would be possible.…”
Section: Fasd or Fasds?mentioning
confidence: 99%